Synergistic antibacterial activity and inhibition of TiO2 nanotube arrays and loaded antibiotics against gram-positive and gram-negative bacteria - Opolot, Emmanuel Einyat; Wang, Haochen; Capadona, Jeffrey R.; von Recum, Horst A.; Amani Hamedani, Hoda (Frontiers in Biomaterials Science, 2024)
Implantable medical devices continue to be vulnerable to bacterial infections. The unrelenting formation of antibiotic resistant bacterial strains not only exacerbates these infections but also renders the current treatment strategies impotent. The need is greater than ever for innovative and effective approaches to counteract drug-resistant bacteria. This study examines the innate antibacterial properties of TiO2 nanotube arrays (TNAs) and their ability to locally deliver antibiotics to inactivate gram-positive and gram-negative bacteria, in vitro. Using a two-step electrochemical anodization process, TNAs with a diameter of ~100 nm and a length of ~5 µm were grown on titanium substrates. After 24 hours of incubation, as-fabricated TNAs showed 100% clearance of Escherichia coli , and 97% clearance of Staphylococcus aureus growth. The antibiotic-loaded TNAs demonstrated sustained slow-release of cefotaxime and imipenem measured over 14 days. In vitro bacterial studies revealed the capability of cefotaxime-and imipenem-loaded TNAs in completely inhibiting the growth with 100% clearance of Klebsiella pneumoniae after 24 and 48 hours of incubation. Bacterial inhibition assay revealed a significantly enlarged inhibition zone difference of 18 mm around the imipenem-loaded TNAs against Klebsiella pneumoniae compared to the as-fabricated TNAs which was maintained for 7 days with ~ 10 µg. mL -1 of antibiotic released from the TNAs which was found to be lower than the dose required to completely eradicate multidrug resistant bacteria when used in conjunction with the antibacterial TNAs. The results of our study highlight the potential of TNAs as a versatile platform for addressing treatment strategies related to bacterial infections and antibiotic resistance in implantable medical devices.